FUNCTIONAL-SEMANTIC CHARACTERISTICS CONNECTING PREPOSITIONS OF THE KAZAKH AND TURKISH LANGUAGES - З. Шaдкaм; Ж.М. Кокеевa (Journal of Oriental Studies, 2019)
This article discusses the semantic nature and function of connecting prepositions in the Ka zakh and Turkish languages in a comparative aspect. Connecting prepositions not only words in the considered languages, they also connect homogeneous members in a sentence and sentences in compound sentences. Therefore, they (prepositions) are primarily a semantic link between words and sentences. Thus, prepositions in the Kazakh and Turkish languages are used between homogeneous members and members of the compound sentences (CS) and are presented in several forms. One type of union that is actively functioning in two Turkic languages is a connecting prepositions (in Kazakh men, ben, pen, menen), da, de, ta, te, jane, and in Turkish ile, ve, dahi, da, ise, ki, bile) detailed the study and analysis of which is devoted to this article. Key words: language, lexicology, prepositions, connecting prepositions, semantic structure.